2013
DOI: 10.1162/jocn_a_00415
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Objects through the Language Glass

Abstract: Abstract■ Recent streams of research support the Whorfian hypothesis according to which language affects oneʼs perception of the world. However, studies of object categorization in different languages have heavily relied on behavioral measures that are fuzzy and inconsistent. Here, we provide the first electrophysiological evidence for unconscious effects of language terminology on object perception. Whereas English has two words for cup and mug, Spanish labels those two objects with the word "taza."We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 64 publications
5
61
1
Order By: Relevance
“…Holmes et al, 2009;Maier et al, 2014;Thierry et al, 2009). Even though the effect as such is numerically small, this result is relevant, because it helps to bridge the gap between the behavioral benefit associated with CP and electrophysiological signatures found in the present and several previous studies (Boutonnet et al, 2013;Forder et al, 2017;Holmes et al, 2009;Mo, Xu, Kay, & Tan, 2011;Thierry, 2016;Thierry et al, 2009), by showing behavioral and ERP effects in the same task.…”
Section: Behavioral Categorical Perception Effectsupporting
confidence: 58%
See 1 more Smart Citation
“…Holmes et al, 2009;Maier et al, 2014;Thierry et al, 2009). Even though the effect as such is numerically small, this result is relevant, because it helps to bridge the gap between the behavioral benefit associated with CP and electrophysiological signatures found in the present and several previous studies (Boutonnet et al, 2013;Forder et al, 2017;Holmes et al, 2009;Mo, Xu, Kay, & Tan, 2011;Thierry, 2016;Thierry et al, 2009), by showing behavioral and ERP effects in the same task.…”
Section: Behavioral Categorical Perception Effectsupporting
confidence: 58%
“…One recent study found color CP in the P1 component to predict access to visual consciousness in the attentional blink paradigm . Other studies found CP effects starting in the N1 time range (Boutonnet, Dering, Vinas-Guasch, & Thierry, 2013;Thierry et al, 2009;Yu et al, 2017), interpreted as a visual mismatch negativity, suggesting an effect of linguistic categories on preattentive perception (Thierry et al, 2009). In the context of visual object perception, the N1 is usually seen as an indicator of configural processing during early visual perception (Rossion & Jacques, 2011;Tanaka & Curran, 2001).…”
Section: Electrophysiological Correlates Of Categorical Perceptionmentioning
confidence: 99%
“…These results suggest a stronger perceptual discrimination of a linguistically encoded, but task-irrelevant visual contrast. In a similar vein, Boutonnet, Dering, Viñas-Guasch, and Thierry (2013) studied effects of language on object perception. Whereas English distinguishes between cups and mugs, Spanish has one label for both items (taza).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we will examine at what level of processing these effects may arise, i.e., at the level of judgement, attention or core perception (see Firestone & Scholl, 2016;Raftopoulos, 2017). In order to fully exploit the categorizing function of language, we will adopt a picture-matching paradigm, rather than a target detection paradigm (used in Boutonnet et al, 2013;Thierry et al, 2009). These latter studies involved paradigms with only one exemplar of the category of interest (e.g., a circle, a cup) and participants were exposed to this exemplar for a large number of trials, limiting the generalizability of their results (see Maier, Glage, Hohlfeld, & Abdel Rahman, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation